ANALISIS KEBIASAAN BELAJAR SISWA BERPRESTASI DI SD NEGERI 013 MUARA JALAI - Nurfadila, Nurfadila; Ananda, Rizki; Aprinawati, Iis (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2021)
The purpose of the study was to find out how the study habits of outstanding students at school, at home and the differences in study habits of outstanding students at SD Negeri 013 Muara Jalai were. This research uses case study qualitative research. The research subjects were high achieving students in grades IV and V of SD Negeri 013 Muara Jalai, class teachers, principals, parents of high achieving students and the neighborhood of high achieving students. Data collection techniques are observation, interviews, documentation and field notes. The main instrument is the researcher using tools in the form of observation guidelines, interviews, documentation and field notes. Data analysis using the Miles and Huberman model. The technique of checking the validity of the data is by using triangulation techniques. The results of the study showed that the learning habits of students excel in the school environment. Students attend class on time, students follow lessons by paying attention, listening, taking notes, asking questions, concentration and discipline in learning. While the study habits of students excel at home. Outstanding students have a schedule of study hours, during the learning process students are always guided and accompanied by their parents, students always prepare their study needs at night and always leave in the morning. The difference in the study habits of high achieving students is when they study at home, namely during study hours